The Effectiveness of Acupuncture on Myofascial Trigger Points Versus Traditional Chinese Medicine Acupoints for Treating Plantar Fasciitis With Low Back Pain: A Study Protocol for a Randomised Clinical Trial [Letter] - Wang J; Qi W; Tian J (Journal of Pain Research)
Jia Wang,1 Wenxia Qi,1 Jiexiang Tian2 1Graduate School of Gansu University of Chinese Medicine, Lanzhou, Gansu, 730000, People’s Republic of China; 2Affiliated Hospital of Gansu University of Chinese Medicine, Lanzhou, Gansu, 730000, People’s Republic of ChinaCorrespondence: Jia Wang, Raduate School of Gansu University of Chinese Medicine, Lanzhou, Gansu, 730000, People’s Republic of China, Email dxxc02@outlook.com